Theft on trial: Prosecution, conviction and sentencing patterns in colonial Victoria and Western Australia. Issue 1 (March 2017) - Piper, Alana; Durnian, Lisa
From Ned Kelly to Waltzing Matilda, tales of thievery dominate Australia's colonial history. Yet while theft represents one of the most pervasive forms of criminal activity, it remains an under-researched area in Australian historical scholarship. This article draws on detailed inter-jurisdictional research from Victoria and Western Australia to elaborate trends in the prosecution, conviction and sentencing of theft in colonial Australia. In particular, we use these patterns to explore courtroom attitudes towards different forms of theft by situating such statistics within the context of contemporary commentaries. We examine the way responses to theft and the protection of property were affected by colonial conditions, and consider the influence of a variety of factors on the outcomes of theft trials.